Perceived Stress among Iranians during COVID-19 Pandemic; Stressors and Coping Mechanisms: A Mixed-methods Approach. (December 2022) - Faghankhani, Masoomeh; Sodagari, Faezeh; Shokrani, Marjan; Baradaran, Hamid Reza; Adabi, Alimohammad; Zabihi, Masoud; Adeli, Aliyeh Mahdavi; Fathimakvand, Mahdi; Golalipour, Elahe; Aghdasi, Sina; Javanbakht, Arash; Nadoushan, Amir Hossein Jalali
Objective: New coronavirus (COVID-19) pandemic socioeconomically affected the world. In this study, we measured the perceived stress in response to the COVID-19 pandemic among Iranians to determine the groups at both extremes of the spectrum followed by identifying the stressors and coping mechanisms. Methods: This study was a mixed-methods study. We distributed a web-based 10-item perceived stress scale (PSS-10), to measure perceived stress score (PSS), through social networks from March 12 to 23, 2020. Then, we interviewed 42 students, 31 homemakers, 27 healthcare providers, and 21 male participants to identify the sources of stress and coping mechanisms. Results: Finally, 13, 454 participants completed the questionnaires. The median and interquartile range (IQR) of the participants' PSS was 21 (15-25). Students, homemakers, and healthcare workers (HCWs) showed a higher median (IQR) of PSS compared to other groups (23 [18 to 27], 22 [16 to 26], and 19 [14 to 24], respectively). Male participants showed a lower median (IQR) PSS (17 [12 to 23]). Content analysis of 121 participants' answers showed that the most common stressors were school-related issues mentioned by students, family-related issues mentioned by homemakers, and COVID-19-related issues mentioned by healthcare providers. Male participants' coping mechanisms were mostly related to the perception of their abilities to cope with the current crisis. Conclusion: Our participants clinically showed a moderate level of PSS. The main stressors among students, homemakers, and HCWs were related to their principal role in this period, and male participants' coping mechanisms were inspired by the self-image retrieved from the social perspectives.